Pemanas Kue Pukis Otomatis Berbasis Mikrokontroler - Ali Basrah Pulungan; Hamdani Hamdani; Hastuti Hastuti; Arzi Afriyanda (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
The development of modern technologies and automation of electronic devices today makes work easier. For example in the temperature control system on a heater that is designed more automatically, in the manufacture of this Pukis cake heater, it is supported by supporting components such as atmega 32 microconroler as a control center for pukis cake heaters, thermocouple sensors as temperature detectors, heater as heating element, fan as regulator of air circulation on the heater, the keypad functions as a medium input temperature setting on the heater, LCD as a display media output on the heater, and the Buzzer as an alarm on the baking cake heater. In the design of the baking pan, the tool can work well and in accordance with what the author plans.